(untitled) - Carl A. Burtis; David E. Bruns; consulting editor Barbara G. Sawyer (St. Louis, Missouri, 2015)
A condensed, easier-to-understand student version of the acclaimed Tietz Textbook of Clinical Chemistry and Molecular Diagnostics, Tietz Fundamentals of Clinical Chemistry and Molecular Diagnostics, 7th Edition uses a laboratory perspective in providing the clinical chemistry fundamentals you need to work in a real-world, clinical lab. Coverage ranges from laboratory principles to analytical techniques and instrumentation, analytes, pathophysiology, and more. New content keeps you current with the latest developments in molecular diagnostics. From highly respected clinical chemistry experts Carl Burtis and David Bruns, this textbook shows how to select and perform diagnostic lab tests, and accurately evaluate results
Includes bibliographical references and index
Keywords: Clinical chemistry; Molecular diagnosis